English as a Medium of Instruction and Its Effect on Local Cultural Identities - Alzahrani, Amal (International Journal of Language and Literary Studies, 2026)
This study examines the advantages and challenges of employing English as a medium of instruction (EMI) in an international school in Riyadh, Saudi Arabia. The study aims to examine the impact of EMI on the development of students’ local cultural identity. The participants of the study are four female students attending an international middle school. Data were collected through semi-structured interviews and focus group discussions. Findings revealed both positive and negative impacts of EMI on students’ identities. While EMI had minimal influence on students’ religious or cultural values, it significantly affected their Arabic literacy and language preferences. The study highlights the complex relationship between language, culture, and identity in international school settings. It explains the challenges students face in maintaining their Arabic fluency. Results contribute to understanding cultural identity development and suggest the need for further research on EMI’s broader implications in the Saudi context.